A percepção da influência da gestão estratégica de pessoas no comprometimento organizacional pelos docentes do ensino superior - Ventura, Vera Lúcia da Silva (2012)
The present study aimed at investigating higher education teachers‟ perceptions on the strategic people management and organizational commitment constructs in a Higher Education Institution. The study was designed by the qualitative research nature as well as by the phenomenological method by means of the case study research tool. For data collection, interviews, participant observation and documentary analysis through semi-structured scripts were carried out. These data were treated by the following procedures: content analysis. The research was conducted in three phases. First of all, it was evaluated the institution objectives and goals and to characterize the people management policies regarding training and development, payment, incentives and rewards, as well as promotion and career. Secondly, the affective, instrumental and normative approaches of the organizational commitment of teachers regarding the institution that was investigated were characterized. And lastly, differences in perception of strategic people management and of organizational commitment among teachers of undergraduate and post-graduate studies were verified. For reaching that purpose, 20 teachers of higher education, divided into 16 teachers of undergraduate and 4 of post-graduate studies, were interviewed. Of the respondents, 3 of them also have the role of academic managers. The research findings indicate that, based on the respondents‟ perception, the strategic people management influences teachers‟ commitment towards the institution and their professional mission as teachers. The results also show that undergraduate teachers perceive that influence with greater emphasis on affective commitment, whereas post-graduate studies teachers demonstrate the perception of that influence with greater relevance regarding the normative commitment. Backed by the theoretical framework, the study made it possible to associate the commitment to autonomy and to rationalization tion in teachers‟ work as well, thus presenting two different outcomes. On the one hand, it was perceived, in the first one, a link between work autonomy and focus on both affective and normative commitments caused by the commitment management strategies. On the other hand, it was observed, in the second one, an association between work rationalization and instrumental approach led by the management strategy of control. These findings indicate the importance of having a balance of these strategies in managing people in order to get the alignment of the organizational commitment of higher education teachers with institutional goals.